Recent advances in thermochemical conversion of biomass - Pandey, Ashok; Bhaskar, Thallada; Stöcker, Michael (Chemist); Sukumaran, Rajeev (Elsevier, 2015)
Provides information on the most advanced and innovative biohydrogen technology Useful as reference book Provides examples on large scales and commercial applications of biohydrogen processes Useful for researchers intending to study sacle-up Provides information on integration of process and technology on biohydrogen Useful for researchers and industry A book designed as a text book not merely a collection of research articles Useful as text book for graduate students and reference book for researchers.
Keywords: Biomass conversion.; Biomass energy.; Thermochemistry.; elektronické knihy; electronic books